The doppelgänger : literature's philosophy - Vardoulakis, Dimitris (Fordham University Press, 2010)
This title presents literature as the double of philosophy. This relation is historically rooted in the genesis of the doppelganger as literature's response to the philosophical focus on subjectivity.